G219 Hydrocortisone tablets: human factors in manipulation and their impact on dosing accuracy. (12th March 2018) - Watson, C; Kerr, S; Davies, J; Stirling, H; Webb, E; Batchelor, H
Abstract : Background: Exposure to deficient or excess glucocorticoids is associated with increased morbidity in patients with adrenal insufficiency. An age-appropriate low dose hydrocortisone formulation is not available and manipulation of adult medication is required with potential for inaccurate dosing. Licensed pharmaceutical products must contain ±10% of labelled drug content. Aims: To assess the variability in manipulation procedures undertaken by parents/carers and to quantify the dose-variability in the manipulated product based on the method of preparation. Methods: Parents of children with adrenal insufficiency completed a survey assessing the methods used to manipulate hydrocortisone 10 mg tablets. A sub-group were asked to manipulate a scored 10 mg hydrocortisone tablet (Auden Mackenzie brand) to provide the prescribed dose for their child as they would at home. Hydrocortisone content was analysed according to the current European Pharmacopoeial method. Results: One hundred and twenty-nine parents completed the questionnaire. Overall 55% of parents break or cut the tablet and 43% suspend the tablet in water prior to administration. 34% are prescribed a dose indivisible by 2.5 mg of whom 33% break the tablet to acquire the dose. Twenty-seven parents/carers participated in the sub-study and the target doses they prepared ranged from 0.5–7.5 mg. Forty eight percent of the preparations were within 10% of the target dose; 74% were within 20% and 82% were within 30%. Based on this small sample size the most accurate method of tablet manipulation is to split the tablet along the score lines. However, this is only possible for doses divisible by 2.5 mg. Dispersion of the tablet in water and withdrawal of the relevant volume was associated with poor accuracy. Conclusions: Children are at risk of suboptimal dosing when parents/carers are required to manipulate adult products to provide the appropriate dose to children. This risk is greatest when doses need to be prepared via dispersion of a tablet and calculation of the volume to withdraw. This may be related to the poor solubility of hydrocortisone which makes formation of a homogenous liquid difficult. There is a need for age-appropriate hydrocortisone products to be available to children. Acknowledgement: This study was funded via an unrestricted research grant from Diurnal Ltd.